PENERAPAN METODE PROBLEM BASED, EXPERIENCE DAN EXPERIENTIAL LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA KULIAH KEWIRAUSAHAAN - Yulius Koesworo; Anna Triwijayati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
Decreasing the motivation and learning outcome forwards entrepreneurship subject motivates the expertise and academician to create learning athmosphere of entrepreneurship condusively.This research is briefly stress to describe study activities of entrepreneurership learning in faculty of economic Widya Mandala Surabaya. The method implemented in this neglance are problem based method, experience and experiential learning. Also, identification of restriction in this method is conducted. Morover, students are subject and patner in this research. They are supported to participate actively in aims to increase learning outcome. Condusive learning athmosphere is a motivator of more variation of student activities. As a result, learning evaluation shows that student’s mark in odd semester 2003/4 is 3.310 in average standart deviation 0.3848, flowerer, student’s mark in odd semester 2004/5 is 3.359 in average with standart deviation 0.3189, respectively. Eventhough, studen’s mark in average after implementation of new method is better than before implementation, but the differences between mean marking is not significant.